196k views
0 votes
G(x) = -x^3+4
f(x)=4x-2
find (f-g) (3x)

1 Answer

3 votes

Answer:

(f-g) (3x)=27x^3+12+2

Explanation:

First lets write the following:

(f-g) (3x)= f(3x)-g(3x)

Now we need to find equivalent expression for f(3x) and for g(3x), we will obtaine them by evaluating 3x instead of x in every 'x' appearance.

Wi have>

g(3x)= -27x^3+4

f(x)=12x-2

Now, lets perfomr the desired operation.

f(3x)-g(3x)=27x^3+12+2

User Al Lelopath
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.